Deviation from target capital structure : evidence from large acquisitions - Lange, Franziska (2019)
The thesis studies target capital structures in the context of 1,290 acquisitions. In particular, the thesis analyses whether firms have target leverage ratios and whether they affect the choice of payment in the transaction. It illustrates that overleveraged bidders are less likely to pay for the acquisition with cash only. Moreover, the thesis examines the post-acquisition changes within the firm’s capital structure and its adjustment speed. Addressing the change of target leverage after the transaction, the results suggest that managers consider the future target leverage of the combined firm in their acquisition’s financing choices. Firms with high growth opportunities use the merger-induced change in target leverage for leverage adjustment, to a greater extent than firms with smaller growth opportunities. Firms tend to adjust their market leverage towards target by 39% every year, on average. Taking into account the leverage effect of the merger, it is shown that about 47% of an acquirer’s leverage deviation caused by the merger is reversed after five years. Collectively, the results of the thesis support a capital structure model with a target ratio.